A comunicação científica no ambiente virtual: desvelamento do ecossistema - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
The goal of this study is to present and discuss the use of electronic tools as a means of science communication by assessing the existing tools and observing and describing which tools are appropriate for diffusion/interaction and storage processes, as well as their communicative ecosystem. The study shows the communicational flows and points negative and positive aspects involved. It discusses the science communication scenario, from the traditional means to the new configuration in digital media, the cycle of scientific production, the changes in the digital context and the impact of such context in recent times. The study approaches the post-industrial era and the information society as a mark for the development of information and communication technologies. It defines networks as an instrument of interaction and sharing. It presents Web 2.0 as a platform for social networks and electronic tools and highlights their contribution to science communication. The concept of ecosystem is borrowed from biology, applied to the science communication process and highlighted in the functions of the electronic tools available in the virtual environment. The study describes the available tools as emerging models for supporting science diffusion, classifying them as diffusion/interaction, storage and measurement tools, presenting the players and structures involved in the communication process.
Keywords: Comunicação científica; Ferramentas eletrônicas; Web 2.0; Science Communication; Electronic Tools; CIÊNCIAS SOCIAIS APLICADAS: COMUNICAÇÃO